2018
DOI: 10.3892/ol.2018.8484
|View full text |Cite
|
Sign up to set email alerts
|

Tudor‑staphylococcal nuclease regulates the expression and biological function of alkylglycerone phosphate synthase via nuclear factor‑κB and microRNA‑127 in human glioma U87MG cells

Abstract: Abstract. Glioma is one of the malignant tumor types detrimental to human health; therefore, it is important to find novel targets and therapeutics for this tumor. The downregulated expression of Tudor-staphylococcal nuclease (SN) and alkylglycerone phosphate synthase (AGPS) can decrease cancer malignancy, and the overexpression of them can the increase viability and migration potential of various tumor cell types; however, the role of AGPS in the proliferation and migration of glioma, and the association of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…mTOR prevented the cardiomyocyte necrosis and inflammation but was conducive to functional recovery in ex vivo hearts [44]. CircZNF292 served as a tumor-promoting factor through the mTOR signaling pathway, relying on the expressions of the alkylglycerone phosphate synthase (AGPS) in glioma cells [45]. In addition, previous investigation has reported that the BNIP3 is capable of inhibiting the sensitivity of the mTOR, which plays pivotal roles in autophagic induction.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR prevented the cardiomyocyte necrosis and inflammation but was conducive to functional recovery in ex vivo hearts [44]. CircZNF292 served as a tumor-promoting factor through the mTOR signaling pathway, relying on the expressions of the alkylglycerone phosphate synthase (AGPS) in glioma cells [45]. In addition, previous investigation has reported that the BNIP3 is capable of inhibiting the sensitivity of the mTOR, which plays pivotal roles in autophagic induction.…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of glioma cells into normal brain tissue can destroy normal brain tissue function. In the early stage, it may show irritation symptoms such as localized epilepsy, 10 BioMed Research International and later, it may show symptoms of neurological deficits such as paralysis, which is a sign of deterioration of glioma and the main cause of treatment failure and death [14]. Abnormally expressed lipids can regulate a series of functional genes to turn on and/or off abnormally by participating in the formation of tumor cells and signal transduction process so that tumor cells can acquire various characteristics different from normal cells and induce cell canceration and tumor proliferation, invasion, and apoptosis resistance [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Tudor-SN is transcriptionally activated by the TGFb and NF-jB pathways [70,73,85] but also participates in the regulation of the gene transcription of TGFb and NF-jB pathway-related members [28,[86][87][88][89]. The PI3K-AKT-mTOR pathway can regulate the translation of the Tudor-SN protein [76], and components of this pathway can also be induced and activated by high Tudor-SN expression [87,90,91]. It is thus hypothesized that activation of the TGFb, NF-jB, and PI3K-AKT-mTOR pathways in tumor cells mediates the overexpression of Tudor-SN by regulating the processes of RNA transcription and protein translation, and the upregulation of Tudor-SN expression, in turn, facilitates the activation of these signaling pathways.…”
Section: Role Switching Modelmentioning
confidence: 99%